Analisis Pengaruh DPK, CAR, NPF Dan ROA Terhadap Pembiayaan Di PT Bank Muamalat Indonesia TBK. Periode 2007-2013 - RADIS AGISTA, ARISTANTIA, Ir. Maulidyah Indira H., MS. (2015)
This study was conducted to determine the effect of third party funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Return on Assets (ROA) of the Financing in PT Bank Muamalat Indonesia Tbk. 2007-2013 period simultaneously and partially. The purpose of this study was to determine the effect DPK, CAR, NPF, and ROA simultaneously and partially to the financing of the PT. Bank Muamalat Indonesia Tbk. the period 2007-2013. File analysis method used is multiple regression analysis with significance value of 0.05 or 5%. From the research, found that the DPK, CAR, ROA NPF and simultaneously affect the financing. The four variables are able to explain the variable financing amounted to 94.81%, and the balance of 5.19% is explained by other factors. Based on t test, DPK and ROA variables significant effect on the financing of the significance of t count equal to 0.0000 and 0.0377 (<0.05), while the variable CAR and NPF t significance of 0.2798 and 0.8082 (> 0.05) so that no significant effect on the variable financing. Keywords: Third Party Fund (DPK), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return on Assets (ROA), Financing.